ANALISIS KESIAPAN PEMERINTAH DAERAH DALAM MENERAPKAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL BERDASARKAN PERMENDAGRI NOMOR 64 TAHUN 2013 PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA KENDARI - Erdiansyah, Dian Rezki (JURNAL AKUNTANSI, 2016)
This study aimed to analyze the readiness of Financial Management Board and the Regional Asset (BPKAD) of Kendari in implementing the Government Accounting Standards (SAP) Accrual Based by Permendagri No.64/2013 seen from several indicators such Readiness Human Resources and Information Systems. Type of research is descriptive qualitative research. The research was conducted by taking object on the Financial Management Board and Asset of Kendari. The type of data used in this study is primary data. Methods of data analysis using qualitative descriptive analysis. Data collection techniques in this study were interviews and observation. The results showed that the Financial Management Board and the Regional Asset (BPKAD) of Kendari in implementing the Accrual Based Government Accounting Standards were quite prepared seen from the indicators Readiness Human Resources and Information Systems. This is supported by many employees who have educational background of accountancy and the technical assistance that has been carried out to the employee BPKAD of Kendari in operating SIMDA applications that are now accrual-based. Keywords: Readiness, Government Accounting Standards, Accrual Basis, Human Resources, and Information Systems